CHARACTERISTIC OF SHALE GAS RESERVOIR USING LMR (LAMBDA-MU-RHO) INVERSION: CASE STUDY BARNETT SHALE, FORT WORTH BASIN TEXAS, USA - Hagayudha Timotius; Yulinar Firdaus (BULLETIN OF THE MARINE GEOLOGY, 2013)
The decreasing of fossil fuel reserves in the conventional reservoir has made geologists and geophysicists to explore alternative energy source that could answer energy needs in the future. Therefore the exploration of oil and gas that is still trapped in the source rock (shale) is needed, and one of them still developed in shale gas. The method of Amplitude Versus Offset (AVO) Inversion is used for Lambda-Mu-Rho attributes, that is expected to assess values of physical parameters of shale. Fort Worth Basin is chosen to be a study area because, the Barnett Shale Formation has proven contains of oil and gas. This study using synthetic seismic data, based on geological model and well log data obtained from Vermylen (2012). It is expected from the study of Barnett Shale that related to shale gas development could be applied. Keyword: Shale gas, Barnett Shale, Fort Worth Basin, AVO Inversion, Lambda-mu-rho attributes Penurunan cadangan bahan bakar fosil pada reservoar konvensional membuat ahli geologi dan geofisika mengeksplorasi sumber energi alternatif guna menjawab kebutuhan energi di masa depan. Oleh karena itu dibutuhkan eksplorasi minyak dan gas yang masih terperangkap dalam batuan induk (serpih), dan salah satunya yang dikembangkan saat ini adalah â€œshale gasâ€. Penggunaan metode inversi Amplitudo Versus Offset (AVO) untuk atribut Lambda-Mu-Rho diharapkan dapat menghasilkan nilai-nilai parameter â€œfisis shaleâ€. Cekungan Fort Worth dipilih sebagai lokasi penelitian ini karena terdapat Formasi â€œBarnett Shaleâ€ yang telah terbukti mengandung minyak dan gas. Penelitian ini menggunakan data seismik sintetik berdasarkan model geologi serta data sumur yang diperoleh dari Vermylen (2012). Diharapkan dari penelitian tentang Barnett Shale yang berkaitan dengan pengembangan shale gas dapat diaplikasikan. Kata kunci: â€œShale gasâ€, â€œBarnett Shaleâ€, Cekungan Fort Worth, Inversi AVO, atribut Lambda-Mu-Rho